A Comparative Analysis of the Theory of Regulation and The Social Structure of Accumulation Theory - Kotz, David M.; Department of Economics; University of Massachusetts (Boston, MA US: University of Massachusetts, 1988)
Contiene una recopilación de lecturas de teoría microeconómica.
Keywords: TEORIA ECONOMICA; ECONOMIA; MICROECONOMÍA